Are we missing lifetime COPD diagnosis among people with COPD recorded death? A population- based retrospective cohort study. Issue 4 (2022) - Gayle, Alicia; Lenoir, Alexandra; Minelli, Cosetta; Quint, Jennifer
No abstract available